EU human rights and democratization policies achievements and challenges - Gomez Isa, Felipe; Churruca, Cristina; Wouters, Jan (Routledge/UACES contemporary European studies, 2018)
The contributions to the book were discussed as a seminar organized by the Institute of Human Rights at the University of Deusto (Bilbao, Spain) on "Challenges to the Effectiveness of EU Human Rights and Democratization in April 2016.